2007
DOI: 10.1080/00015458.2007.11680084
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic Artery Aneurysm. Case report

Abstract: Hepatic artery aneurysms represent about 20% of all visceral aneurysms and 0.01-0.2% of all arterial aneurysms. The authors report on a good risk patient with small infra-renal aortic aneurysm (AAA) and a large hepatic artery aneurysm. An excision and vein grafting of the hepatic artery aneurysm has been performed. The authors made a survey of recent literature concerning hepatic artery aneurysms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
22
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(22 citation statements)
references
References 24 publications
0
22
0
Order By: Relevance
“…2,3,5,9 It has been reported that extrahepatic aneurysms are located in the common hepatic artery in 63% of reported cases, in the right hepatic artery in 28% of cases, in the left hepatic artery in 5% of cases, and in both the right and left hepatic arteries in 4% of cases. [3][4][5]8,10 Furthermore, a general trend has been noted in which intrahepatic aneurysms tend to be located in the right hepatic artery. 4 The aneurysmal diameters reported have ranged between 1.5 and 14 cm, with the mean diameter being calculated at 3.6 cm.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…2,3,5,9 It has been reported that extrahepatic aneurysms are located in the common hepatic artery in 63% of reported cases, in the right hepatic artery in 28% of cases, in the left hepatic artery in 5% of cases, and in both the right and left hepatic arteries in 4% of cases. [3][4][5]8,10 Furthermore, a general trend has been noted in which intrahepatic aneurysms tend to be located in the right hepatic artery. 4 The aneurysmal diameters reported have ranged between 1.5 and 14 cm, with the mean diameter being calculated at 3.6 cm.…”
Section: Discussionmentioning
confidence: 99%
“…4 The aneurysmal diameters reported have ranged between 1.5 and 14 cm, with the mean diameter being calculated at 3.6 cm. 9 HAAs are solitary in 92% of cases and multiple in 8% of cases, 2,[8][9][10] and about one third of HAA patients present with other visceral artery aneurysms. 3,5,8,10 Although HAA has been diagnosed in all age groups and both sexes, most patients are adults (age range, 20-80 years) and male.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations